2017
DOI: 10.3389/fimmu.2017.01374
|View full text |Cite
|
Sign up to set email alerts
|

The Kynurenine Pathway As a Novel Link between Allergy and the Gut Microbiome

Abstract: In the past few decades, the indoleamine 2,3 dioxygenase (IDO) subset of the kynurenine (KYN) pathway of tryptophan (TRP) metabolism has been the subject of much research in the area of immune tolerance. In this review, we aim to incorporate new findings on this pathway in relation to allergy and the gut microbiome, while providing a comprehensive overview of the pathway itself. Stimulated by interferon gamma, IDO acts as a tolerogenic, immunosuppressive enzyme to attenuate allergic responses by the induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 121 publications
2
73
0
Order By: Relevance
“…Decreased tryptophan and increased kynurenine concentrations, and increased KT ratios, have been reported during infections in animal models, 25 likely due to increased IDO1 activity during inflammation, which may serve to deprive pathogens of essential amino acids (i.e., tryptophan) necessary for growth and proliferation, and regulate T-cell activity, leading to immunological tolerance (i.e., decreases in tryptophan decrease T-cell proliferation at sites of inflammation, leading to decreased activity of T cells). 62 The negative association of the KT ratio with T-cell concentrations observed in the present study was not entirely unexpected as higher plasma tryptophan could well be associated with better maintenance of T-cell homeostasis in healthy individuals, although such data have not been reported previously, to the best of our knowledge. The positive association of the KT ratio with memory CD8 T cells was unexpected but could represent a positive association of kynurenine production during undiagnosed infections in some of our study participants (e.g., viral infections) that would cause an expansion of activated CD8 T cells (which would be CD45RO + ) in blood.…”
Section: Discussionsupporting
confidence: 54%
“…Decreased tryptophan and increased kynurenine concentrations, and increased KT ratios, have been reported during infections in animal models, 25 likely due to increased IDO1 activity during inflammation, which may serve to deprive pathogens of essential amino acids (i.e., tryptophan) necessary for growth and proliferation, and regulate T-cell activity, leading to immunological tolerance (i.e., decreases in tryptophan decrease T-cell proliferation at sites of inflammation, leading to decreased activity of T cells). 62 The negative association of the KT ratio with T-cell concentrations observed in the present study was not entirely unexpected as higher plasma tryptophan could well be associated with better maintenance of T-cell homeostasis in healthy individuals, although such data have not been reported previously, to the best of our knowledge. The positive association of the KT ratio with memory CD8 T cells was unexpected but could represent a positive association of kynurenine production during undiagnosed infections in some of our study participants (e.g., viral infections) that would cause an expansion of activated CD8 T cells (which would be CD45RO + ) in blood.…”
Section: Discussionsupporting
confidence: 54%
“…Proteomic, genomic, and metabolomics studies have recently observed the ability of oxidized amino acids to modulate gene expression, leading to impaired physiological functions (Li, Shi, Le, Ding, & Zhao, ; Yang, Zhang et al., ; Yang, Yan et al., ,). Finally, animal proteins, heme iron and derived protein oxidation products may alter the microbiome, making the intestinal mucosa more sensitive to both biological and chemical threats (Constante, Fragoso, Calvé, Samba‐Mondonga, & Santos, ; Portune et al., ; Van der Leek, Yanishevsky, & Kozyrskyj, ). As follows, the most recent scientific evidences of the role of dietary oxidized proteins on particular pathological disorders are reported.…”
Section: Pathogenesis Of Dietary Protein Oxidation: Recent Advancesmentioning
confidence: 99%
“…This metabolic cascade can be catalyzed by three enzymes, namely, indoleamine 2,3-dioxygenase 1 (IDO1), IDO2, and tryptophan 2,3-dioxygenase (TDO2). [1][2][3][4] IDO1 is by far the beststudied among these enzymes, as it was the first interferon (IFN)-activated gene to be described as early as in the late 1970s. 5 The differential distribution and activity of IDO2 and TDO2 calls for further investigation to elucidate to which extent IDO2 and TDO2 contribute to Trp catabolism in vivo.…”
Section: Introductionmentioning
confidence: 99%